Effect of banana intake on serum potassium level in patients undergoing maintenance hemodialysis: A randomized controlled trial - Zilin Quan; Caixia Li; Liyan Zhao; Dongmei Cui; Shuangxin Liu; Yan Yin; Qi Tang; Dehan Zeng; Li Song; Xia Fu (Elsevier, 2024)
Objective: This study aimed to assess the effect of banana intake during hemodialysis on serum potassium levels in maintenance hemodialysis (MHD) patients. Methods: This study was a single-center, randomized controlled clinical trial conducted from September 15 to December 15, 2021, at a tertiary hospital in southern China. A total of 126 MHD patients were randomly assigned to either the intervention group (n = 64) or the control group (n = 62). Patients in the intervention group consumed approximately 250 g of bananas during hemodialysis, while those in the control group did not consume any food during hemodialysis. Demographic information and hemodialysis-related parameters were collected through case information collection before hemodialysis. Laboratory indicators (such as complete blood count, biochemical indicators, inflammation markers, liver function, kidney function, etc.) were evaluated by collecting pre-hemodialysis blood samples from patients. Serum potassium and blood glucose levels were measured at 2 h and 4 h of hemodialysis, as well as before the next hemodialysis session, and hemodialysis-related complications were recorded. The blood potassium and blood glucose indicators during hemodialysis were compared using repeated measures analysis. Results: A total of 122 MHD patients completed the study (61 in each group). The results showed that there was no significant interaction between group and time on serum potassium levels. However, serum potassium levels in the intervention group were higher than those in the control group at 2 h (3.9 ± 0.5 mmol/L vs. 3.6 ± 0.3 mmol/L, P < 0.01) and 4 h (3.5 ± 0.4 mmol/L vs. 3.3 ± 0.3 mmol/L, P < 0.01) of hemodialysis. There was no interaction between group and time on blood glucose levels. The incidence of arrhythmias (8.2% vs. 29.5%, P = 0.003) and hypokalemia (52.5% vs. 80.3%, P = 0.002) during hemodialysis was significantly lower in the intervention group compared to the control group. Conclusion: Consuming approximately 250 g of bananas at the start of hemodialysis does not lead to hyperkalemia. It can effectively reduce the incidence of hypokalemia and arrhythmias, and prevent a rapid decline in serum potassium levels during hemodialysis.